Predictors of second revascularization in patients with history of coronary artery bypass graft - Gholamreza Davoodi (Research in Cardiovascular Medicine, 2018)
Objective: The number of individuals with a history of coronary artery bypass graft surgery (CABG) who may require a second revascularization intervention is growing. We aimed to identify the predictors of revascularization in patients with a history of CABG who were referred for conventional coronary angiography due to acute coronary syndrome (ACS) or stable angina. Methods: Data of 536 patients (74% males) who had a previous history for CABG and were referred for coronary angiography due to ACS or stable angina were included in the study. Demographic, clinical, diagnostic, and angiographic characteristics of the patients were retrieved from our institutional databank and patient's records. Based on the final recommendation, the patients were divided into two groups for either medical treatment or revascularization and compared for the study variables as well as identifying the predictive factors for the second revascularization. Results: From a total of 536 patients, 194 (36.1%) patients were advised to continue medical therapy, and the rest were referred for revascularization (repeat CABG or percutaneous coronary intervention). Elapsed time after CABG for <1 year or >10 years (P = 0.016), use of diuretics (P = 0.002), and presenting in an inpatient setting (P = 0.009) were significant predictors for the feasibility of second revascularization treatment, using multiple regression analysis. Conclusion: Elapsed time after CABG and some other clinical factors can predict the feasibility of the second revascularization in patients with a history of CABG and new onset of cardiac symptoms.